Pengembangan Multimedia Interaktif Nearpod Pada Materi Ancaman Terhadap Negara Dalam Bingkai Bhineka Tunggal Ika Kelas X IPS SMAN 9 Muaro Jambi - Aswita, Yeni; Sutja, Akmal; Usmanto, Heri (Citizenship Education, Faculty of Education, Jambi University, 2023)
This research is motivated by the lack of teacher using learning media in the learning process of civic education so that students ecome less enthusiastic in learning.the purpose of this research is to develop Nearpod interactive multimedia on material threats to the state withing the ftamework of bhineka tunggal ika in order to improve the learning qulity of students in class X social science at senior high school 9 Muaro Jambi. The type of method used in this study is a research and development method that uses the ADDIE model as it’s development model. The results of this research and development obtained the results of material expert validation with a score of 50 and a percentage of 89%, language validation obtained a score of 42 with a percentage of 89,5%, and validation by media experts obtained a score of 58 with a percentage of 96%. Based on this percentage, the media developed by the district is categorized as worthy to be tested. Then the results of individual trials with a score of 54 and a percentage of 90% were obtained in the very feasible category, small group trial abtained a score af 616 with a percentage of 91% and categorized as very good, and the large group trial obtained a score of 2.025 with a percentage of 90% and can be categorized as very good. Based on the results obtained in this research and development, it can be conclouded that Nearpod interactive multimedia can be used by teachers and students in learning civic education, material threats of bhineka tunggal ika in class X senior high school 9 Muaro jambi.